Genome-Wide Histone Modifications and CTCF Enrichment Predict Gene Expression in Sheep Macrophages - Massa, Alisha T.; Mousel, Michelle R.; Herndon, Maria K.; Herndon, David R.; Murdoch, Brenda M.; White, Stephen N. (Frontiers in Genetics, 2021)
Alveolar macrophages function in innate and adaptive immunity, wound healing, and homeostasis in the lungs dependent on tissue-specific gene expression underepigenetic regulation. The functional diversity of tissue resident macrophages, despite their common myeloid lineage, highlights the need to study tissue-specific regulatory elements that control gene expression. Increasing evidence supports the hypothesis that subtle genetic changes alter sheep macrophage response to important production pathogens and zoonoses, for example, viruses like small ruminant lentiviruses and bacteria like Coxiella burnetii. Annotation of transcriptional regulatory elements will aid researchers in identifying genetic mutations of immunological consequence. Here we report the first genome-wide survey of regulatory elements in any sheep immune cell, utilizing alveolar macrophages. We assayed histone modifications and CTCF enrichment by chromatin immunoprecipitation with deep sequencing (ChIP-seq) in two sheep to determine cis-regulatory DNA elements and chromatin domain boundaries that control immunity-related gene expression. Histone modifications included H3K4me3 (denoting active promoters), H3K27ac (active enhancers), H3K4me1 (primed and distal enhancers), and H3K27me3 (broad silencers). In total, we identified 248,674 reproducible regulatory elements, which allowed assignment of putative biological function in macrophages to 12% of the sheep genome. Data exceeded the FAANG and ENCODE standards of 20 million and 45 million useable fragments for narrow and broad marks, respectively. Active elements showed consensus with RNA-seq data and were predictive of gene expression in alveolar macrophages from the publicly available Sheep Gene Expression Atlas. Silencer elements were not enriched for expressed genes, but rather for repressed developmental genes. CTCF enrichment enabled identification of 11,000 chromatin domains with mean size of 258 kilobases. To our knowledge, this is the first report to use immunoprecipitated CTCF to determine putative topological domains in sheep immune cells. Furthermore, these data will empower phenotype-associated mutation discovery since most causal variants are within regulatory elements.